Triglyceride: A mediator of the association between waist-to-height ratio and non-alcoholic fatty liver disease: A second analysis of a population-based study - Hu, Haofei; Han, Yong; Liu, Yufei; Guan, Mijie; Wan, Qijun (Frontiers in Endocrinology, 2022)
Objective: Increasing evidence suggests that an increased waist-to-height ratio (WHtR) may increase the risk of non-alcoholic fatty liver disease (NAFLD). Whether this association is due to WHtR itself or mediated by WHtR-associated increases in triglyceride (TG) is uncertain. On that account, our research aims to disentangle these relationships. Methods: In this cross-sectional study, 14251 participants who participated in the medical examination program were consecutively and non-selectively collected in Murakami Memorial Hospital in Japan from 2004 to 2015. The independent and dependent variables were WHtR and NAFLD, respectively. Triglyceride was the mediating factor. The correlation between WHtR, TG, and NAFLD risk factors was examined using spearman correlation analysis. The association between WHtR or TG and NAFLD was examined using multiple logistic regression. In order to determine whether TG mediated the association between WHtR and NAFLD, a mediation analysis was performed. Results: The mean age of the included individuals was 43.53 ± 8.89 years old, and 7411 (52.00%) were male. The mean WHtR and TG were 0.46 ± 0.05, 0.89 ± 0.63, respectively. The prevalence rate of NAFLD was 2507 (17.59%). Individuals with NAFLD had significantly higher levels of WHtR and TG than those without NAFLD (P<0.05). After adjusting covariates, the multivariate linear regression analysis showed that WHtR was positively associated with TG. That was, for every 0.1 increase in WHtR, TG increased by 0.226mmol/L (β=0.226, 95%CI: 0.206, 0.247). Multiple logistic regression analysis indicated that WHtR (OR=8.743, 95%CI: 7.528, 10.153) and TG (OR=1.897, 95%CI: 1.732, 2.078) were positively associated with NAFLD. The mediation analysis showed that WHtR had a direct, significant effect on NAFLD (β=0.139, 95%CI: 0.126, 0.148), and TG partially mediated the indirect effect of WHtR on NAFLD (β=0.016, 95% CI: 0.013-0.019). TG contributed to 10.41% of WHtR-related NAFLD development. Conclusion: Findings suggest a mediation link between WHtR and TG and the risk of NAFLD. The significance of TG as a mediator deserves recognition and consideration.